Concentrations of antimony in infants dying from SIDS and infants dying from other causes. Issue 3 (1st March 2000) - Cullen, A; Kiberd, B; Devaney, D; Gillan, J; Kelehan, P; Matthews, T G; Mayne, P; Murphy, N; O'Regan, M; Shannon, W; Thornton, L
Abstract : OBJECTIVES: Raised concentrations of antimony have been found in infants dying of sudden infant death syndrome (SIDS). The presumed source of this antimony is toxic gases generated from fire retardants that are present in cot mattresses. The aim of this study was to determine the role of antimony in SIDS. DESIGN: Samples of liver, brain, serum, and urine were collected from all patients dying from SIDS and a group of aged matched control infants who had died of other causes. SETTING: Nationwide study in Ireland. SUBJECTS: 52 infants dying from SIDS and 19 control infants aged > 7 days and < 1 year. RESULTS: The median concentration of antimony in the liver and brain of infants dying of SIDS was < 1 ng/g, with no difference detected between the infants dying from SIDS and the control infants. The range of antimony in the serum of infants dying of SIDS was 0.09–0.71 μg/litre (median, 0.26). Although no difference was found between infants dying from SIDS and control infants, SIDS infants were found to have higher concentrations when compared with healthy infants in the 1st year of life, probably as a result of release of antimony into serum after death. Urine antimony concentrations in infants dying from SIDS were < 3.91 ng/mg (corrected for creatinine) and similar to values found both in control infants and healthy infants. CONCLUSION: There is no evidence to support a causal role for antimony in SIDS.